Effect of Applied Voltage in Electron Density of Homogeneous Dielectric Barrier Discharge at Atmospherice Pressure - Shrestha, R.; Tyata, R. B.; Subedi, D. P. (Himalayan Physics, 2013)
A homogeneous dielectric barrier discharge (DBD) was produced in air with a mixture with argon by applying high voltage A.C. source of potential difference (0-20) kV and frequency (20-50) kHz across two parallel disc electrodes with glass as dielectric barrier. In this paper, the determination of electron density in glow mode based on power balanced method is presented. Significant effects in electron density were found with the variation applied voltage. The Himalayan Physics Vol. 4, No. 4, 2013 Page: 10-13 Uploaded date: 12/22/2013